In light of the new legislation for per- and polyfluoroalkyl substances, can continued food sustainability be achieved? - Senovilla-Herrero, Diana; Moore, Heather; Service, Matthew; Thomas, Ray; Helyar, Sarah; Mbadugha, Lenka; Campbell, Katrina (Frontiers in Sustainable Food Systems, 2024)
Per-and polyfluoroalkyl substances (PFAS) are a group of persistent organic pollutants which pose significant risks to human health and the environment. This article comprehensively examines the implications of new legislation concerning PFAS for food sustainability. The current legislative frameworks governing PFAS in food production and distribution are explored, highlighting the need for robust mitigation strategies to safeguard food safety and environmental integrity. It delves into the challenges posed by the legislation, raising questions about the balance between environmental protection and the sustainability of the food system. It provides a review of the state-of-the-art analytical methods for PFAS detection and quantification in water and food matrices. Their advantages and limitations are discussed, offering valuable insights for researchers in the field. In addition, a range of mitigation strategies to combat PFAS contamination in the food supply chain are explored. By collating current knowledge on PFAS contamination in sustainable food systems, this article aims to provide a comprehensive resource for researchers, policymakers, and practitioners striving to ensure the safety and sustainability of our global food supply. The integration of legislative insights, advanced analytical techniques, and practical mitigation approaches offers a holistic perspective on managing PFAS-related challenges in the context of sustainable food systems.